Recent Progress in Intrinsically Stretchable Sensors Based on Organic Field-Effect Transistors - Mingxin Zhang; Mengfan Zhou; Jing Sun; Yanhong Tong; Xiaoli Zhao; Qingxin Tang; Yichun Liu (Sensors)
Organic field-effect transistors (OFETs) are an ideal platform for intrinsically stretchable sensors due to their diverse mechanisms and unique electrical signal amplification characteristics. The remarkable advantages of intrinsically stretchable sensors lie in their molecular tunability, lightweight design, mechanical robustness, solution processability, and low Young’s modulus, which enable them to seamlessly conform to three-dimensional curved surfaces while maintaining electrical performance under significant deformations. Intrinsically stretchable sensors have been widely applied in smart wearables, electronic skin, biological detection, and environmental protection. In this review, we summarize the recent progress in intrinsically stretchable sensors based on OFETs, including advancements in functional layer materials, sensing mechanisms, and applications such as gas sensors, strain sensors, stress sensors, proximity sensors, and temperature sensors. The conclusions and future outlook discuss the challenges and future outlook for stretchable OFET-based sensors.